Levosimendan for sepsis-induced myocardial dysfunction: friend or foe? - Du, Xinxin; Xiong, Fang; Hou, Yafei; Yu, Xiangyou; Pan, Pengfei (Frontiers in Cardiovascular Medicine, 2025)
Sepsis-induced myocardial dysfunction (SIMD) involves reversible myocardial dysfunction. The use of inotropes can restore adequate cardiac output and tissue perfusion, but conventional inotropes, such as dobutamine and adrenaline, have limited efficacy in such situations. Levosimendan is a novel inotrope that acts in a catecholamine-independent manner. However, study results regarding the treatment of SIMD with levosimendan are inconsistent, and the use of levosimendan is highly controversial. In this review, we summarized the therapeutic mechanisms of levosimendan in SIMD and considered recent research on how to improve the efficacy of levosimendan in SIMD. We also analyzed the potential and limitations of levosimendan for the treatment of SIMD to provide ideas for future clinical trials and the clinical application of levosimendan in SIMD.